The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.15177/seefor.16-09
|View full text |Cite
|
Sign up to set email alerts
|

Partnerships for Urban Forestry and Green Infrastructure Delivering Services to People and the Environment: A Review on What They Are and Aim to Achieve

Abstract: Background and Purpose: Partnerships are a key mechanism in the planning, delivery and management of urban forestry (UF) and green infrastructure (GI). They can facilitate locally rooted co-management and polycentric governance. They can also achieve synergies by combining the resources, commitment and expertise of diverse stakeholder groups in order to generate valuable outcomes and build social capital. Unfortunately, the term "partnerships" is not used consistently in literature and requires clarification. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
(117 reference statements)
0
1
0
4
Order By: Relevance
“…U cijelom procesu važno mjesto moraju imati civilne inicijative, i naravno ukupna zainteresovana javnosti -stanovništvo grada BL. Sukob i preplitanje interesa koji trenutno postoje, a vezano za predmetni objekat, se jedino može riješiti saradnjom zainteresovanih strana, odnosno: Grad, JPŠ, Zavod, civilno društvo i stanovništvo; a uz uvažavanje interesa: turizma, sporta, kulture (pored turizama, sporta i rekreacije, zaštite prirode i kulturno i istorijskog naslijeđa, jasne veze uočavamo i sa sektorima zdravstvene zaštite, prosvetom i naukom) (Ralph et al, 2016).…”
Section: Rezultati I Diskusija / Results and Discussionunclassified
See 2 more Smart Citations
“…U cijelom procesu važno mjesto moraju imati civilne inicijative, i naravno ukupna zainteresovana javnosti -stanovništvo grada BL. Sukob i preplitanje interesa koji trenutno postoje, a vezano za predmetni objekat, se jedino može riješiti saradnjom zainteresovanih strana, odnosno: Grad, JPŠ, Zavod, civilno društvo i stanovništvo; a uz uvažavanje interesa: turizma, sporta, kulture (pored turizama, sporta i rekreacije, zaštite prirode i kulturno i istorijskog naslijeđa, jasne veze uočavamo i sa sektorima zdravstvene zaštite, prosvetom i naukom) (Ralph et al, 2016).…”
Section: Rezultati I Diskusija / Results and Discussionunclassified
“…Uz pretpostavku o poznavanju savremenih pojmova u šumarskoj nauci, a vezano za funkcije šuma, održivo upravljanje šumskim resursima, višenamjensko šumarstvo (koje u svoje upravljačke ciljeve pored proizvodnih realizuje i OKFŠ 2 ) (Blagojević et al, 2016;Ralph et al, 2016) izvršili smo analizu aktuelnih normativnih i planskih akata koji su u direktnoj vezi sa upravljanjem ovim šumama.…”
Section: Izvodunclassified
See 1 more Smart Citation
“…However, several authors mention that green spaces may play an important role in attracting tourists to urban areas, e.g., by enhancing the attractiveness of cities and as a complement to other urban attractions (Majumdar et al, 2011), or that aesthetic, historical and recreational values of urban parks increase the attractiveness of the city, in its promotion as tourist destination, thus generating employment and revenues (Chiesura, 2004). Hansmann et al (2016) also showed that tourism is one of the objectives of urban forest partnerships that are becoming increasingly popular around Europe.…”
Section: Urban Tourism and Ugi Usesmentioning
confidence: 99%
“…Este procedimiento se relaciona a la gestión sostenible en sus diferentes escalas políticas y espaciales (Pérez-Medina & López-Falfán, 2015;Ragheb et al, 2022). Así en el ámbito local, es posible a través de la planificación, administración, el marco normativo y su monitoreo -procesos que forman parte de una gobernanza efectiva-; obtener un máximo beneficio para la ciudad (Hansmann et al, 2016;Reyna, 2017).…”
Section: Introductionunclassified